2016
DOI: 10.1111/jfpp.12932
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Osmo-Convective Dehydration Process for Dry Tomato Production

Abstract: The aim of this study was to evaluate the sensorial and nutritional quality of dried tomato, obtained by osmotic dehydration and drying, using the experimental design to optimize process conditions. Tomatoes of Ap variety were dehydrated in osmotic solution, prepared with sodium chloride (0-10%) and sucrose (3.96-46%), after being dried at the kiln, at temperatures from 56.6 to 73.4C. A central composite rotational design (CCRD) 2 3 was used to evaluate the effects of osmotic solution concentration, immersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The variable °Hue forms an angle of 180° with titratable acidity and lycopene being strongly negatively correlated [ 39 ] evaluating the quality of dried tomatoes through osmotic dehydration and drying, found that the lycopene content reduced with storage time for both packages, with air and vacuum. Since lycopene is responsible for the red color of tomatoes, this led to a loss of intensity and color change, a decrease in the chroma coordinate, and an increase in °Hue.…”
Section: Resultsmentioning
confidence: 99%
“…The variable °Hue forms an angle of 180° with titratable acidity and lycopene being strongly negatively correlated [ 39 ] evaluating the quality of dried tomatoes through osmotic dehydration and drying, found that the lycopene content reduced with storage time for both packages, with air and vacuum. Since lycopene is responsible for the red color of tomatoes, this led to a loss of intensity and color change, a decrease in the chroma coordinate, and an increase in °Hue.…”
Section: Resultsmentioning
confidence: 99%